Development Of An Interactive Digital Module Based On Local Wisdom To Support The Independent Learning Curriculum For Grade VI - Hutagalung, S. Lamriana; Hutagalung, Insenalia S.R; Siagian, Yosua Marasi Parningotan; Purba, Lydia (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to develop an interactive digital module based on local wisdom as an alternative learning medium to support the implementation of the Merdeka Belajar Curriculum in elementary schools. The background of this research is based on the need for contextual, engaging learning media that can instill local cultural values in students from an early age. The method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The trial subjects in this study were fourth-grade students of GKPS Rambungmerah Private Elementary School in an area with a rich local culture. The module was developed by combining thematic curriculum content with folklore, traditional games, and regional songs, packaged in an interactive digital application-based format. Validation results by material and media experts indicated that the module had very good feasibility, while field trials showed increased learning motivation, material understanding, and positive attitudes towards local culture. These findings indicate that an interactive digital module based on local wisdom can be an effective, relevant learning innovation, and in line with the spirit of Merdeka Belajar.